O Programa Bolsa Família e o direito fundamental à segurança pública: uma análise à luz da economia do crime de Gary Becker - Andrade, Carlos Henrique de Lima (2022)
The objective of this article is to discuss the Bolsa Família Program (PBF) as a public policy of effectiveness of the fundamental right to public security, based on Gary Becker's Economic Theory of Crime. The increase of crime rates has aroused a feeling of insecurity and, therefore, greater attention from members of the Powers of the Republic who are required to solve the problem. In response, given the complexity of the criminal phenomenon, several measures are adopted, especially the mass incarceration that results from provisional and definitive prisons, in addition to large investments in public security. Despite this, satisfactory results have not been observed in reducing crime. Gary Becker's theory, therefore, is placed as an instrument for the analysis of public policies necessary to combat crime, considering its methodological rigor. This research is exploratory and will be developed from bibliographic research, notably scientific articles with empirical studies of interest to the proposed theme. In this way, through the assumptions of the aforementioned theory, the Bolsa Família Program, despite not being sufficient, if individually considered, is characterized as an important public policy to combat the criminal phenomenon, by increasing the costs of crime in counterpoint to the eventual benefits and, consequently, encourage the reduction of crime.